2015
DOI: 10.1155/2015/531906
|View full text |Cite
|
Sign up to set email alerts
|

Children with Autism Spectrum Disorder and Patterns of Participation in Daily Physical and Play Activities

Abstract: Autism spectrum disorder (ASD) indicates several neurodevelopmental impairments which may end in impairments in motor or physical activities. Daily physical activity involvement was investigated in a total of 83 children (52 boys and 31 girls) with ASD aged 6–15 years. Results indicated that only 10 (12%) of children with ASD were physically active. Children were predominantly engaged in solitary play rather than social play activities. Gender, family income, and household structure were found to be associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0
15

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(107 citation statements)
references
References 49 publications
6
86
0
15
Order By: Relevance
“…The most current evidence indicates that children and adolescents with ASD are not sufficiently active and fall short of meeting the Center for Disease Control's Physical Activity Guidelines (Bandini et al, 2013; Obrusnikova & Cavalier, 2011; Memari et al., 2015; McDonald, Esposito & Ulrich, 2011). Several studies have found that youth with ASD are less physically active than their typically developing (TD) peers (McCoy, Jakicic, & Gibbs, 2016; Pan et al.…”
mentioning
confidence: 99%
“…The most current evidence indicates that children and adolescents with ASD are not sufficiently active and fall short of meeting the Center for Disease Control's Physical Activity Guidelines (Bandini et al, 2013; Obrusnikova & Cavalier, 2011; Memari et al., 2015; McDonald, Esposito & Ulrich, 2011). Several studies have found that youth with ASD are less physically active than their typically developing (TD) peers (McCoy, Jakicic, & Gibbs, 2016; Pan et al.…”
mentioning
confidence: 99%
“…It would be beneficial to carry out further research into this area using a neuro typical control group of participants who do not attend the weekly “Monday Club” sessions, to compare the scores of physical activity between the two groups (Memari et al, 2015) and to further test the GARS-3 measure which has shown to be sensitive to changes in ASD severity over time.…”
Section: Discussionmentioning
confidence: 99%
“…As first ASD symptoms [37,38] that should be verified are the following: the child does not present pronounced smiles or other happiness expressions at the age of six months; at the age of nine months, the child shares neither sounds, smiles, nor other facial gestures; continuing at about twelve, with the absence of chatters and of concrete gestures like greeting, indicating or showing. At the age of sixteen months, he does not articulate words and at twenty-four, he is unable to formulate phrases of two words that have meaning if they are not for pure repetition [39]. This process presents, without any doubt, enough variants, both in the present symptoms and in its appearance, therefore, its detection and follow-up are important.…”
Section: Diagnosis Of Autismmentioning
confidence: 99%